Caracterização microbiológica e análise da pesca de peixes ornamentais recifais. - Borges, Lucas Daniel (2020)
Aquarism is the practice of creating fish, invertebrates, plants and other aquatic organisms in aquariums or ponds for ornamentation purposes. Marine ornamental fish species are widely bred globally, being displayed in more than two million public aquariums in countries around the world. On certain occasions, when there is an inadequate management of ornamental fish fishing to supply the aquarium market, there has been a decline in the health of the environments and the presence of stressors that act on the local fauna, causing the appearance of epizootic diseases. This work aims to characterize the microbiology of reef fish and the environment after fishing. This work reserves the focus on three genres well described to the importance of the theme - Vibrio, Aeromonas and Pseudomonas. The present study observed a gradual decrease in the population of Cultivable Heterotrophic Bacteria (BHC) in the containment system of the animals caught due to the considerable technical failures observed. Bacteria of the genera Vibrio, Aeromonas and Pseudomonas were isolated and identified, from samples of the fish's mucus and water from the animals' containment system after fishing. The antimicrobial susceptibility test showed that the genus Aeromonas was the one with the highest number of resistant strains, 8% of which had their resistance profile framed as MDR. The mucus of the analyzed fish demonstrated that it can inhibit the adhesion or the development of pathogens. The use of microbiological analyzes in the fishing of ornamental fish allowed to mediate the process of preservation of fishing in a more enriching way, motivating the conservation of the resource and contributing to the development of a really significant economic activity.